High-Power, Wavelength-Locked 878.6 nm In-Band Pumped, Acoustic-Optically Q-Switched Nd:YVO4 MOPA Laser With TEM00 Mode - Qiang Liu; Mingming Nie; Fuyuan Lu; Mali Gong (IEEE Photonics Journal, 2016)
In this paper, a wavelength-locked 878.6-nm pumped acoustic-optically Q-switched Nd:YVO4 laser is presented. A master oscillator power amplifier configuration with two-stage amplifiers is employed to scale the output power. Both the oscillator and the power amplifiers are directly pumped by a wavelength-locked 878.6-nm laser diode, reducing the thermal load of the laser crystal. The maximal output power is 120.8 W at the repetition rate of 100 kHz, with the $\text{M}^{2}$ factor of 1.31 and 1.30 in two directions. The maximal pulse energy of 4.85 mJ and the shortest pulsewidth of 15 ns are achieved at the repetition rate of 20 kHz, with near diffraction limited output. The global optical–optical efficiencies are 37.7% and 47% at the repetition rate of 20 and 100 kHz, respectively. The laser has excellent output stability in a specific range of time and temperature. The output power is very stable during the five operating hours, and it is insensitive to the temperature variation of the water chiller from 15 °C to 35 °C.